DEVELOPMENT, CHARACTERIZATION AND SKIN IRRITATION OF MANGOSTEEN PEEL EXTRACT SOLID DISPERSION CONTAINING CLAY FACIAL MASK - Pan-on, Suchiwa; Rujivipat, Soravoot; Ounaroon, Anan; Kongkaew, Chuenjid; Tiyaboonchai, Waree (International Journal of Applied Pharmaceutics, 2018)
Objective: To develop a clay facial mask containing mangosteen peel extract solid dispersion (MPESD) for enhancing Î±-mangostin bioavailability and to determine suitable clay-based facial mask. Methods: The MPESD were prepared by a melting-solvent method employing PVP K30 and poloxamer 188 as a carrier. The water solubility was determined by HPLC method. The in vitro skin permeability was examined using porcine ear epidermis. The effects of clay types on the physical stability of MPESD and Î±-mangostin adsorption capacity were evaluated. The skin irritation was determined by 4 h human patch test. Results: After dissolved optimal formulation of MPESD in water, the spherical micelle was observed with a mean size of ~150 nm and showed significantly Î±-mangostin water solubility enhancement of ~7 mg/ml, 700 times greater than MPE. Upon mixing the MPESD with clays, a dry powder was obtained. In vitro permeation studies of the MPESD mixed with titanium dioxide showed lowest Î±-mangostin permeation, while MPESD mixed with mica or talcum showed similar permeation profile as free MPESD solutions. No sign of skin irritation was observed in volunteers after application of the MPESD-based clay facial mask patch on the inner forearm skin for 4 h. Conclusion: MPESD demonstrates a promising technique for improving water solubility and permeation of Î±-mangostin which reducing the staining effect. In addition, it is safe for topical application and cosmetically acceptable.